Project Based Learning Embedded with Entrepreneurship in Physics Learning to Improve Physics Application Ability - Ananda Aprlilia; Sukardiyono Sukardiyono; Jumadi Jumadi; Suparwoto Suparwoto; Rahayu Dwisiwi Sri Retnowati; Wipsar Sunu Brams Dwandaru (Postgraduate, University of Mataram, 2024)
This study aimed to determine the effectiveness and effect size of project-based learning (PjBL) model embedded with entrepreneurship in online physics learning to improve the physics application ability of senior high school students; and to describe students' responses to the entrepreneurship embedded PjBL model. This was a quasi-experimental study. The experimental design used was the clustered pretest-posttest controlled group design, which involved two groups and the sampling was carried out in clusters. This research was conducted at SMA Negeri 1 Mlati Yogyakarta on the subject of Elasticity and Hooke's Law. Data collection techniques in this study used tests and questionnaires. Data analysis utilized descriptive and inferential analysis. The results of the study showed that the application of the entrepreneurship embedded PjBL model was effective for improving students’ physics application ability in the moderate category. The effect size of the entrepreneurship embedded PjBL model towards the physics application ability was in the moderate category. Finally, the student responses toward the entrepreneurship embedded PjBL model were in the very good category.